2010
DOI: 10.1016/j.foodchem.2010.05.077
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene-rich fractions derived from pink guava by-product and their potential activity towards hydrogen peroxide-induced cellular and DNA damage

Abstract: a b s t r a c tEffects of solvent and supercritical carbon dioxide (SC-CO 2 ) extraction on antioxidant and cytotoxic activities of lycopene-rich fractions of decanted pink guava by-product (decanter) were determined with lycopene-equivalent antioxidant capacity, b-carotene bleaching and MTT (3-(4,5-dimethylthiazol-2yl)-2,5-diphenyl tetrazolium bromide) assays. Extraction with SC-CO 2 gave a higher yield than solvent extraction (3.15 vs. 0.68 mg/100 g dried decanter, corresponding to 42.99 and 33.63 mg of lyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Numerous studies have indicated the health benefits of consuming lycopene and demonstrated its preventive role in a number of chronic diseases including various types of cancers (Agarwal & Rao, 2000;Bhuvaneswari & Nagini, 2005;Cohen, 2002;Giovannucci, 2002;Khachik et al, 2002). This carotenoid phytonutrient is found to be the most effective antioxidant among all tested carotenes and xanthophylls (Atessahin et al, 2007;Di Mascio et al, 1989;Hekimoglu et al, 2009;Kong et al, 2010). It offers important health benefits, particularly, in regard to prostate, lung, heart, liver and skin health.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated the health benefits of consuming lycopene and demonstrated its preventive role in a number of chronic diseases including various types of cancers (Agarwal & Rao, 2000;Bhuvaneswari & Nagini, 2005;Cohen, 2002;Giovannucci, 2002;Khachik et al, 2002). This carotenoid phytonutrient is found to be the most effective antioxidant among all tested carotenes and xanthophylls (Atessahin et al, 2007;Di Mascio et al, 1989;Hekimoglu et al, 2009;Kong et al, 2010). It offers important health benefits, particularly, in regard to prostate, lung, heart, liver and skin health.…”
Section: Introductionmentioning
confidence: 99%
“…Lycopene has been shown to regulate gap-junction communication (Zhang et al, 1991), inhibit cancer cell migration (Bhuvaneswari and Nagini, 2005), arrest cell cycle progression (Ford et al, 2011), and modulate several signal transduction pathways (Palozza et al, 2011). Recently, lycopene has received greater attention as a result of studies indicating that it is a highly efficient antioxidant and free radical scavenger (Atessahin et al, 2007;Hekimoglu et al, 2009;Kong et al, 2010). Lycopene has high liposolubility and so can pass through the blood-brain barrier (Khachik et al, 2002), suggesting it may be a potentially useful treatment for brain diseases associated with oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…To make sure that they were not exposed to light, the cuvettes were covered with an opaque aluminium foil. Antioxidant activity was expressed as percentage scavenging capacity and calculated by using the following equation 10 :…”
Section: Ir Measurementmentioning
confidence: 99%